2022
DOI: 10.1002/fsn3.2998
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA improves diabetes‐induced renal fibrosis by regulating the miR‐34‐5p/Notch1 axis

Abstract: The purpose of this study was to evaluate the improvement of tanshinone in renal fibrosis in vitro and in vivo study. It used streptozotocin to model diabetic nephropathy (DN) mice, and treated with different Tanshinone IIA concentrations. The pathology of kidney tissues was evaluated by hematoxylin and eosin (H&E) and Masson's staining; the ultrastructure and apoptosis cell number of kidney tissues were evaluated by transmission electron microscopy (TEM) and TUNEL assay. Relative gene and protein expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…NRF2 is a master regulator for an array of antioxidant responses, and excessive oxidative stress is a well-documented hallmark of COVID-19 pathophysiology ( 34 ). However, in SARS-CoV-2 infection, NRF2 expression is dysregulated and not sufficiently induced to mount an effective antioxidant response ( 35 ). The relative suppression of NRF2 expression is a viral strategy to hijack host protective responses ( 35 ), and pharmacological induction of NRF2 expression is proposed to be an effective strategy against COVID-19 ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…NRF2 is a master regulator for an array of antioxidant responses, and excessive oxidative stress is a well-documented hallmark of COVID-19 pathophysiology ( 34 ). However, in SARS-CoV-2 infection, NRF2 expression is dysregulated and not sufficiently induced to mount an effective antioxidant response ( 35 ). The relative suppression of NRF2 expression is a viral strategy to hijack host protective responses ( 35 ), and pharmacological induction of NRF2 expression is proposed to be an effective strategy against COVID-19 ( 36 ).…”
Section: Resultsmentioning
confidence: 99%
“…NRF2 is a major redox regulator that is significantly induced in response to oxidative stress. Nonetheless, as a component of viral strategy to hijack host protective responses, NRF2 expression is dysregulated during COVID-19, is not sufficiently upregulated, and remains relatively suppressed/minimally induced to mount an effective antioxidant response ( 30 , 35 ). Based on normalization with CypA , we obtained a relatively stable NRF2 induction profile in mild (<2-fold), asymptomatic (<3-fold), moderate (<5-fold), pre-CAM (<13-fold), and post-CAM (<3-fold) groups.…”
Section: Discussionmentioning
confidence: 99%
“…However, Traditional Chinese medicine has a significant effect on the treatment of chronic kidney disease, and some experts suggest that using triptolide and emodin can improve the treatment of proteinuria in the treatment of chronic kidney disease, [16,17] traditional Chinese medicine ingredients such as ginsenosides, tanshinone IIA, anthocyanin also have beneficial effects on DKD. [18][19][20] Xuefu Zhuyu decoction, as the first prescription of promoting blood circulation and removing blood stasis, it has more clinical RCTs for DKD, especially in China. However, there is no systematic review comprehensively describing the effectiveness and safety of Xuefu Zhuyu decoction for DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Zeng et al [ 39 ] used HG-stimulated HK-2 cells in vitro, and the study showed that Tan IIA was able to increase E-cadherin in cells by increasing vitamin D receptor (VDR) protein levels and inhibiting β-catenin and glycogen synthetase kinase-3β (GSK-3β) protein levels and decreased a-SMA expression, thereby attenuating EMT, suggesting that Tan IIA may inhibit the Wnt/β-catenin pathway by upregulating VDR, and thus attenuates high glucose-induced EMT in HK-2 cells. Zhang et al [ 40 ] found that Tan IIA may promote autophagy in the renal tissues of DN rats and HK-2 cells induced by high glucose by regulating the miR-34-5p/Notch1 axis, thereby improving renal tubular fibrosis induced by DN. Wang et al [ 41 ] found that Tan IIA reduced urinary protein excretion and serum creatinine (SCR) levels and attenuated glomerulosclerosis and renal inflammation in CKD rats.…”
Section: Renal Protective Effects Of Tan Iiamentioning
confidence: 99%